1992
DOI: 10.1002/mc.2940050309
|View full text |Cite
|
Sign up to set email alerts
|

Elevated expression of the ribosomal protein S2 gene in human tumors

Abstract: Differential screening of a cDNA library was used to isolate genes differentially expressed in a nontumorigenic clone and a ras-transformed variant of the human teratocarcinoma cell line PA-1. The RNA transcript for one of the cDNA clones that we identified was expressed at a 25-fold higher level in the ras-transformed PA-1 cells than in the nontumorigenic PA-1 cells. DNA sequence analysis of this clone showed that it had 86% nucleic acid homology to the mouse LLRep3 gene and only differed at a single amino ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 44 publications
2
27
0
Order By: Relevance
“…Reports have also been published that observed the altered expression of some ribosomal proteins in human cancers (21)(22)(23)(24)(25). The present study is the first to compare L13 mRNA expression levels in tumor versus normal tissue; it demonstrated that the level of L13 mRNA was higher in 28% of gastric, 41% of colorectal and 20% of liver cancer tissues.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Reports have also been published that observed the altered expression of some ribosomal proteins in human cancers (21)(22)(23)(24)(25). The present study is the first to compare L13 mRNA expression levels in tumor versus normal tissue; it demonstrated that the level of L13 mRNA was higher in 28% of gastric, 41% of colorectal and 20% of liver cancer tissues.…”
Section: Discussionsupporting
confidence: 56%
“…For example, the gene encoding ribosomal protein S19 is mutated in approximately 25% of patients with DiamondBlackfan anemia, which is a rare congenital erythroblastopenia (20). Also, a differential expression of specific ribosomal protein genes was reported earlier as general characteristics of various tumor cell types (21)(22)(23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%
“…For example, several reports have shown that RPS3a and L19 possess oncogenic activities (9). The overexpression of RPS2 has been reported in human squamous cell carcinoma, breast tumor samples (10), and prostate cancer (7). RPS2 is also overexpressed in cells transformed by ras, SV-40, polyoma virus, Rous sarcoma virus, Abelson murine leukemia virus, and chemical carcinogen (11)(12)(13).…”
Section: R E T R a Cmentioning
confidence: 99%
“…Moreover, rp S3 was found to act as an endonuclease in the DNA-repairing system [2]. Finally, some data indicate that tumor diseases may be accompanied by overexpression of rp genes 13,4) and by chromosomal rearrangements in regions of rp genes [ S ] . Therefore, structural analysis of these proteins is necessary for complete understanding of their fundamental role in the cell.…”
mentioning
confidence: 99%